Protest Camps and Repertoires of Contention. (2nd January 2016) - McCurdy, Patrick; Feigenbaum, Anna; Frenzel, Fabian
Abstract : Protest camps have become a prominent feature of the post-2010 cycle of social movements and while they have gripped the public and media's imagination, the phenomenon of protest camping is not new. The practice and performance of creating protest camps has a rich history, which has evolved through multiple movements, from Anti-Apartheid to Anti-war. However, until recently, the history of the protest camp as part of the repertoire of social movements and as a site for the evolution of a social movement's repertoire has largely been confined to the histories of individual movements. Consequently, connections between movements, between camps and the significance of the protest camp itself have been overlooked. In this research profile, we argue for the importance of studying protest camps in relation to social movements and the evolution of repertoires noting how protest camps adapt infrastructures and practices from tent cities, festival cultures, squatting communities and land-based autonomous movements. We also acknowledge protest camps as key sites in which a variety of repertoires of contention are developed, tried and tested, diffused or sometimes dismissed. To facilitate the study protest camps we suggest a theory and practice of 'infrastructural analysis' and differentiated between four protest camp infrastructures: (1) media & communication, (2) action, (3) governance and (4) re-creation. We then use the infrastructures of media and communications as a brief example as to how our proposed infrastructural analysis can contribute to the study of repertoires and our understanding of the rich dynamics of a protest camp.